Electrolyte composition for lithium metal battery with bisalts additives and unit cell containing thereof

KR103020523B1Active Publication Date: 2026-09-15국립군산대학교산학협력단
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240074975
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-10
Publication Date
2026-09-15
Estimated Expiration
2044-06-10

Smart Images

  • Figure 112024062216568-PAT00002_ABST
    Figure 112024062216568-PAT00002_ABST
Patent Text Reader

Abstract

The electrolyte composition for a lithium metal battery according to the present invention is characterized by further comprising: a lithium salt solution comprising a lithium salt and a carbonate-based solvent; and one or more additives selected from lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluoro(oxalato)borate, lithium bisborate, lithium trifluoroacetate, lithium difluoro(bisoxalato)phosphate, and lithium nitrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrolyte composition for a lithium metal battery comprising a bisalt additive and a unit cell comprising the same. Background Technology

[0002] Over the past few decades, lithium-ion batteries have played a significant role in meeting the energy demands of various commercial and residential electronic devices. Nevertheless, lithium-ion batteries are approaching the theoretical energy density limit, which is estimated at about 350 Wh / kg.

[0003] Advanced battery technology has continuously evolved and improved over time to address the diverse requirements of various applications, including portable electronic devices, electric vehicles, and grid-scale energy storage systems. Among these, lithium metal batteries (LMBs) are attracting attention as promising candidates for next-generation energy storage devices due to their excellent theoretical specific capacity (3680 mAh·g) and low electrochemical potential (-0.304V). Despite the remarkable potential of lithium metal batteries, they face several challenges hindering commercialization. One of these is the high reactivity of conventional electrolytes and lithium metal anodes. The uncontrolled growth of lithium dendrites during battery cycling can significantly limit battery cycle life and overall performance by causing internal short circuits, reduced Coulomb efficiency (CE), and safety issues. When considering cathode materials, nickel-rich LiNi 0.8 Co 0.1 Mn 0.1 O2 (NMC811) exhibits an ideal theoretical specific capacity of over 200 mAh / g, which is higher than LiFePO4 (LFP, 170 mAh / g) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC333, 160 mAh / g) and LiNi 0.6 Co 0.2 Mn 0.2It significantly surpasses the capacity of other NMC cathode materials such as O2 (NMC622, 180 mAh / g). Consequently, lithium metal battery systems using lithium metal as the cathode active material and NMC811 as the cathode active material are expected to achieve a specific energy of over 500 Wh / kg at the cell level, which is about 1.5 times greater than the specific energy of lithium-ion batteries currently used in electric vehicles. Nevertheless, nickel-rich layered oxide cathode materials can generate highly reactive transition metal ions, which can cause adverse side reactions with the electrolyte.

[0004] Solving these problems is essential to fully utilize the potential of lithium metal batteries and to commercialize them. Consequently, it is important to develop solid electrolyte interphase (SEI) and cathode electrolyte interphase (CEI) layers to protect the anode and cathode, and researchers are making various efforts to build stable SEI / CEI layers and improve battery stability. Prior art literature

[0005] Journal of Alloys and Compounds, 2021, 876, 159966 “Insight into wide temperature electrolyte based on lithiumdifluoro (oxalate)borate for high voltage lithium-ion batteries ”Angewandte Chemie, 2023, 62, e202216312 “Low Concentration Sulfolane-Based Electrolyte for High Voltage Lithium Metal “Batteries” The problem to be solved

[0006] The objective of the present invention is to provide an electrolyte composition for a lithium metal battery that overcomes the problems of conventional lithium metal batteries through the addition of additives and forms stable SEI and CEI layers when applied to a battery, thereby providing excellent discharge capacity and cycling stability. means of solving the problem

[0007] The electrolyte composition for a lithium metal battery according to the present invention is characterized by comprising: a lithium salt solution comprising a lithium salt and a carbonate-based solvent; and one or more additives selected from lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluoro(oxalato)borate, lithium bisborate, lithium trifluoroacetate, lithium difluoro(bisoxalato)phosphate, and lithium nitrate.

[0008] In an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, the additive may be characterized by being added in an amount of 1 to 5 weight percent relative to the lithium salt solution.

[0009] In an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, the lithium salt may be characterized as being lithium bis(trifluoromethanesulfonyl)imide.

[0010] In an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, the lithium salt concentration of the lithium salt solution may be characterized as being 0.8 to 1.2 M.

[0011] In an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, the carbonate-based solvent may be characterized by comprising one or more selected from ethylene carbonate, ethylmethyl carbonate, dimethyl carbonate, diethyl carbonate, and propylene carbonate.

[0012] In an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, the additive may be characterized by comprising lithium difluoro(oxalato)borate or lithium difluoro(bisoxalato)phosphate.

[0013] The present invention also provides a unit cell, and the unit cell according to the present invention comprises an electrolyte composition, a lithium metal negative electrode, a positive electrode, and a separator according to one embodiment of the present invention.

[0014] A unit cell according to one embodiment of the present invention may be characterized by having an initial discharge capacity of 100 mAh / g or more.

[0015] A unit cell according to one embodiment of the present invention may be characterized by having a Coulomb efficiency of 90% or more.

[0016] A unit cell according to one embodiment of the present invention may be characterized by having a discharge capacity of 70 mAh / g or more after 200 cycles at a charging rate of 0.5 C and a discharging rate of 1 C. Effects of the invention

[0017] The electrolyte composition for a lithium metal battery according to the present invention comprises a lithium salt solution including a lithium salt and a carbonate-based solvent; and one or more additives selected from lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluoro(oxalato)borate, lithium bisborate, lithium trifluoroacetate, lithium difluoro(bisoxalato)phosphate, and lithium nitrate; and when applied to a lithium metal battery, it overcomes the problems of conventional lithium metal batteries and can form stable SEI and CEI layers during battery operation, thereby exhibiting high discharge capacity and cycling stability. Brief explanation of the drawing

[0018] Figure 1 shows the results of measuring the Coulomb efficiency of a battery to which an electrolyte composition for a lithium metal battery according to one embodiment of the present invention is applied. Figure 2 shows the results of testing the cycling performance of a battery to which an electrolyte composition for a lithium metal battery according to one embodiment of the present invention is applied. Figure 3 illustrates the observation of the lithium electrode surface after operation of a cell driven by applying an electrolyte composition for a lithium metal battery according to one embodiment of the present invention. Figure 4 illustrates the lithium electrode observed by XPS (X-ray Photoelectron Spectroscopy) after operation of a cell operated using an electrolyte composition for a lithium metal battery according to one embodiment of the present invention. Figure 5 illustrates the NMC811 electrode observed with a Transmission Electron Microscope (TEM) after operation of a cell driven using an electrolyte composition for a lithium metal battery according to one embodiment of the present invention. Figure 6 illustrates the NMC811 electrode observed by XPS (X-ray Photoelectron Spectroscopy) after operation of a cell driven using an electrolyte composition for a lithium metal battery according to one embodiment of the present invention. Figure 7 illustrates the results of testing the cycling performance after applying an electrolyte composition for a lithium metal battery according to one embodiment of the present invention to a lithium-ion battery. Specific details for implementing the invention

[0019] The advantages and features of the embodiments of the present invention, and the methods for achieving them, will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.

[0020] In describing the embodiments of the present invention, specific descriptions of known functions or configurations will be omitted if it is determined that such detailed descriptions could unnecessarily obscure the essence of the invention. Furthermore, the terms described below are defined in consideration of their functions in the embodiments of the present invention, and these definitions may vary depending on the intentions or practices of the user or operator. Therefore, such definitions should be based on the content throughout this specification.

[0021] The electrolyte composition for a lithium metal battery according to the present invention comprises a lithium salt solution comprising a lithium salt and a carbonate-based solvent; and

[0022] It is characterized by including one or more additives selected from lithium difluorophosphate (LiDFP), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluoro(oxalato)borate (LiODFB), lithium bisborate (LiBOB), lithium trifluoroacetate (LiTFA), lithium difluoro(bisoxalato)phosphate (LiDFBP), and lithium nitrate (LiNO3).

[0023] The electrolyte composition for a lithium metal battery according to the present invention has the advantage of significantly improving the cycling stability of the battery by including one or more of these additives to form a uniform SEI and CEI layer during the operation of the lithium metal battery.

[0024] Specifically, the additive may be included in an amount of 1 to 5 weight percent, preferably 1.5 to 3 weight percent, relative to the lithium salt solution. If the additive is included in a small amount, it is difficult to achieve a sufficient effect of improving cycling stability due to the addition of the additive, and if the additive is included in a large amount, it may inhibit the action of the lithium salt and instead cause a decrease in discharge capacity, etc.

[0025] Preferably, the additive may include two types including lithium difluoro(oxalato)borate or lithium difluoro(bisoxalato)phosphate, and more preferably, may include lithium difluoro(oxalato)borate. By including such an additive, an enhanced cycling stability effect can be exhibited.

[0026] The above lithium salt may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Lithium bis(trifluoromethanesulfonyl)imide). By using LiTFSI, excellent battery performance can be exhibited with high conductivity, and by mixing with the aforementioned additive, high discharge capacity can be exhibited. At this time, the concentration of the lithium salt in the lithium salt solution may be 0.8 to 1.2 M, preferably 0.9 to 1.1 M, and by satisfying this range, the electrolyte composition can exhibit high conductivity.

[0027] The carbonate-based solvent may comprise one or more selected from ethylene carbonate, ethylmethyl carbonate, dimethyl carbonate, diethyl carbonate, and propylene carbonate, and preferably, a mixture of cyclic carbonates such as ethylene carbonate and propylene carbonate and linear carbonates such as ethylmethyl carbonate, dimethyl carbonate, and diethyl carbonate may be used as the solvent. In this case, the cyclic carbonate : linear carbonate may be mixed in a volume ratio of 1 : 1.5 to 3.

[0029] The present invention also provides a unit cell, and the unit cell according to the present invention comprises an electrolyte composition for a lithium metal battery according to one embodiment of the present invention, a lithium metal negative electrode, a positive electrode, and a separator.

[0030] The unit cell according to the present invention has the advantages of high Coulomb efficiency, high discharge capacity, and high discharge capacity retention rate with repeated cycles.

[0031] Preferably, a lithium metal anode having a thickness of 100 to 500 μm may be used. The anode may be any conventional anode used in lithium metal batteries, lithium-ion batteries, or lithium-sulfur batteries without limitation, and the present invention is not limited thereto. Specifically, the anode may include an anode active material, a conductive material, and a binder, and the anode active material may be LiCoO2, LiMnO2, LiNiO2, or LiNi 1-x Co x O2, LiNi 1-x-y Co x Mn y O2, LiNi 1-x-y Co x M y O2 (M is a divalent or trivalent metal), LiFePO4, LiMnPO4, LiCoPO4, and LiFe 1-x M x It may include one or more selected from PO4 (M is a transition metal). The conductive material may include carbon-based conductive materials such as carbon black, carbon nanotubes, and graphene, or metal-based conductive materials such as gold, silver, aluminum, copper, and nickel. The binder may include polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, carboxymethyl cellulose, etc.

[0032] The separator may also be used without limitation if it is a separator that can be conventionally used in lithium batteries, and specifically, it may include a polyethylene or polypropylene separator alone or a separator with a coating layer formed thereon.

[0033] A unit cell according to one embodiment of the present invention may satisfy an initial discharge capacity of 100 mAh / g or more, preferably 120 mAh / g or more, and more preferably 150 to 200 mAh / g, and may have an initial Coulomb efficiency of 90% or more, preferably 95% or more.

[0034] In addition, a unit cell according to one embodiment of the present invention can satisfy a discharge capacity of 70 mAh / g or more, preferably 100 mAh / g or more, and more preferably 120 to 160 mAh / g after 200 cycles at a charging rate of 0.5 C and a discharging rate of 1 C.

[0036] The present invention will be explained in detail below through examples and comparative examples. The following examples are intended only to aid in understanding the present invention, and the scope of the present invention is not limited by the following examples.

[0037] [Example]

[0038] A lithium salt solution with a concentration of 1.0 M was prepared by adding LiTFSI (Lithium bis(trifluoromethanesulfonyl)imide) to a mixed solvent. The mixed solvent used was a mixture of EC (ethylene carbonate), EMC (ethylmethyl carbonate), and DMC (dimethyl carbonate) in a volume ratio of 1:1:1. To prepare a salt additive electrolyte to the prepared lithium salt solution, two types selected from LiDFP (Lithium Difluorophosphate), LiFSI (Lithium Bis(fluorosulfonyl)imide), LiODFB (Lithium difluoro(oxalato)borate), LiBOB (Lithium bisborate), LiPF6, LiTFA (Lithium trifluoroacetate), LiDFBP (Lithium difluoro(bisoxalato) phosphate), and LiNO3 were each added at a concentration of 2 wt% to prepare the electrolyte.

[0039] For convenience of explanation, eight lithium salts (LiDFP, LiFSI, LiODFB, LiBOB, LiPF6, LiTFA, LiDFBP, LiNO3) were abbreviated as D, F, O, B, P, T, L, and N, respectively, and an electrolyte containing 2 wt% LiDFP and 2 wt% LiFSI was denoted as EL-DF.

[0041] [Comparative Example]

[0042] A lithium salt solution with a concentration of 1.0 M was prepared by adding LiTFSI to a mixed solvent. The mixed solvent used was a mixture of EC, EMC, and DMC in a volume ratio of 1:1:1, and the electrolyte of the comparative example is referred to hereinafter as the standard electrolyte, standard electrolyte, or STD.

[0044] Verification of the stability of the lithium metal anode

[0045] The copper electrode was fabricated by punching copper foil to a diameter of 19 mm, and a circular electrode with a thickness of 250 μm and a diameter of 15.6 mm was used for the lithium metal electrode, while polypropylene was used as the separator. Cells were assembled in an argon-filled glove box to evaluate Coulomb efficiency, and the results are shown in Figure 1. Generally, high Coulomb efficiency indicates low reactivity between the electrolyte and the electrode, which means that side reactions are minimized. Referring to the results in Figure 1, the Coulomb efficiency of the standard electrolyte was found to be 72.9%, and it can be confirmed that most electrolytes, excluding EL-DP, exhibit high Coulomb efficiencies. In particular, it can be observed that all electrolytes containing LiPF6 have low Coulomb efficiencies of 80% or less, while the Coulomb efficiencies of EL-DO, EL-FL, EL-OT, and EL-TL all show high values ​​of over 98%. As a result, these bisalt additives can very efficiently form an SEI layer, preventing side reactions and inhibiting dendritic growth.

[0047] Verification of electrochemical properties

[0048] LiNi 0.8 Mn 0.1 Co 0.1 The cycle performance of a cell (Li||NMC811) manufactured using O2 (NMC811, MTI Corporation) and lithium metal as electrodes was verified, and the results are shown in Figure 2.

[0049] An NMC811 electrode with a mass load of 9.0 mg / cm² was used after undergoing a formation cycle at 0.1 C (1.0 C = 200 mAh / g) to build a stable passivation layer on both the NMC811 anode and the lithium metal anode. Subsequent cycles were performed at a charge / discharge current density of 0.5 C / 1.0 C.

[0050] During the formation cycle, the Li||NMC811 cell exhibited a similar discharge capacity of approximately 215 mAh / g; however, subsequent cycling tests confirmed that the discharge capacity of the cell using the STD electrolyte decreased sharply and stabilized at 75 mAh / g after 50 cycles. In contrast, EL-DO demonstrated superior cycling performance, exhibiting a discharge capacity of approximately 162 mAh / g and a capacity retention rate of approximately 94% after 200 cycles. In the case of EL-FL, the discharge capacity dropped sharply to approximately 112 mAh / g after the formation cycle and gradually increased to 125 mAh / g after 75 cycles. However, this discharge capacity did not persist for a long time, exhibiting a capacity retention rate of 61% with a discharge capacity of approximately 68 mAh / g after 200 cycles. The EL-FL cell initially exhibited a Coulomb efficiency of approximately 99%, but this gradually decreased along with a rapid drop in discharge capacity, falling to 83% after 200 cycles; this indicates that serious side reactions are occurring in the cell using EL-FL. The cell using EL-OT exhibited a stable discharge capacity of approximately 162 mAh / g up to 50 cycles, after which the discharge capacity gradually decreased to approximately 125 mAh / g with a capacity retention rate of 77% after 200 cycles. The discharge capacity of the EL-TL gradually increased with repeated cycles prior to capacity stabilization, reaching approximately 150 mAh / g after 120 cycles, which can be attributed to the formation of the CEI layer.

[0051] Figure 2C illustrates the performance of Li||NMC811 cells at various current densities. At the lowest rate of 0.1 C, cells with all electrolytes exhibited a similar capacity of 200 mAh / g, but showed significant differences in rate performance as the current density increased. At a current density of 5.0 C, STD showed 1 mAh / g, EL-DO 143 mAh / g, EL-FL 1 mAh / g, EL-OT 105 mAh / g, and EL-TL 50 mAh / g, indicating that EL-DO has the ability to form stable SEI and CEI layers and inhibit corrosion of the Al current collector. When the rate was lowered back to 0.1 C after the experiment at 5.0 C, it was observed that all electrolytes except STD returned to their initial discharge capacities, while the discharge capacity of the cell with STD decreased significantly. This suggests that the addition of electrolyte additives to EL-DO, EL-FL, EL-OT, and EL-TL demonstrates excellent stability and performance retention effects.

[0053] SEI layer analysis

[0054] To investigate the effects of additive electrolytes in lithium metal batteries, the morphology and composition of the SEI layer on the electrode surface were examined using Scanning Electron Microscope (SEM) and X-ray Photoelectron Spectroscopy (XPS). Specifically, Li||NMC811 coin cells were decomposed after 30 cycles at charge / discharge current densities of 0.5C / 1.0C, and the circulated lithium samples were collected for SEM and XPS analysis. Figure 3 illustrates the surface of an untreated lithium electrode (Fresh Li) and the surfaces of the lithium anodes after circulating cells with STD, EL-DO, EL-FL, EL-OT, and EL-TL electrolytes. The surface of the untreated lithium electrode appears empty and smooth, whereas in STD, heterogeneous layers similar to typical lithium deposition reported in carbonate-based electrolytes and small needle-shaped structures were observed. These needle-shaped structures have the potential to penetrate the separator and cause short circuits. In STD, the growth of lithium dendrites is a result of the formation of a weak SEI layer, which is consistent with the results of Coulomb efficiency and discharge capacity measurements. In contrast, in the case of EL-DO, EL-FL, EL-OT, and EL-TL with added additives, a uniform and densely packed crystalline structure appeared on the surface of the lithium electrode, and this form hinders the penetration of lithium dendrites and can suppress undesirable side reactions between lithium and carbonate-based electrolytes.

[0055] The previously analyzed lithium electrode surface was analyzed by XPS, and the results are shown in Fig. 4. In Fig. 4, the F 1s spectrum shows that STD forms two chemical species, -CF3 and LiF, which occur during the decomposition of LiTFSI; in contrast, the electrolyte with added additives consists of PF, Li x PO y F zIt can be confirmed that additional peaks such as (from the decomposition of LiDFP and LiDFBP) and SF (from LiFSI) are present. LiF is present in the SEI layer of all bisalt additive electrolytes, known for its strong adhesion to the electrode surface, creating a robust and dense SEI layer; LiF is also known to improve Li+ ion diffusivity, thereby reducing surface resistance due to a wide electrochemical stability window. In particular, in EL-DO, EL-FL, and EL-TL, it can be confirmed that i3N and polythionate-type complexes are present in the SEI layer; this configuration has a beneficial effect on rapid lithium ion transport and suppresses electrolyte decomposition on the electrode surface.

[0057] CEI layer analysis

[0058] To evaluate the influence of various electrolytes on the stability of the NMC811 anode, the anode surface was analyzed. The NMC811 anode was detached from the Li||NMC811 cell and observed after 30 cycles at a charge / discharge current density of 0.5C / 1.0C. Figure 5 shows the obtained CEI observed using a Transmission Electron Microscope (TEM). It can be confirmed that a CEI layer of 5 to 17 nm is formed when an electrolyte containing a bisalt additive is applied. The CEI layer of EL-DO has a thickness of 3 to 8 nm, which is more uniform and thinner compared to the CEI layers of STD and other bisalt additive electrolytes. A thin and uniform CEI layer plays a favorable role in lithium ion transport and interfacial charge transfer. The CEI layer was analyzed by XPS, and the results are shown in Figure 6. In Figure 6, the F 1s spectrum indicates that the amount of LiF in EL-DO is the highest among various electrolytes, while the -CF3 signal of EL-DO is the lowest. This can be interpreted as indicating that additives such as LiDFP and LiODFB contained in EL-DO were also decomposed to form LiF.

[0060] Application confirmed in lithium-ion batteries

[0061] To evaluate the compatibility of the bisalt additive in various battery systems, the long-term performance of Gr||NMC811 at a high cutoff voltage of 4.4 V was evaluated, and the results are shown in Fig. 7. Referring to Fig. 7, it can be seen that the discharge capacity is almost impossible to determine when STD is used, and that the discharge capacity of EL-DO is the highest.

Claims

Claim 1 An electrolyte composition for a lithium metal battery comprising: a lithium salt solution containing a lithium salt and a carbonate-based solvent; and an additive; wherein the additive comprises lithium difluorophosphate and lithium difluoro(oxalato)borate, and the lithium difluorophosphate and lithium difluoro(oxalato)borate are each contained in an amount of 1.5 to 3 weight percent relative to the lithium salt solution. Claim 2 delete Claim 3 An electrolyte composition for a lithium metal battery according to claim 1, characterized in that the lithium salt is lithium bis(trifluoromethanesulfonyl)imide. Claim 4 An electrolyte composition for a lithium metal battery according to claim 1, characterized in that the lithium salt concentration of the lithium salt solution is 0.8 to 1.2 M. Claim 5 An electrolyte composition for a lithium metal battery according to claim 1, characterized in that the carbonate-based solvent comprises one or more selected from ethylene carbonate, ethylmethyl carbonate, dimethyl carbonate, diethyl carbonate, and propylene carbonate. Claim 6 delete Claim 7 A unit cell comprising an electrolyte composition according to any one of claims 1 and 3 to 5, a lithium metal negative electrode, a positive electrode, and a separator. Claim 8 In claim 7, the unit cell is characterized by having an initial discharge capacity of 100 mAh / g or more. Claim 9 In claim 7, the unit cell is characterized by having a Coulomb efficiency of 90% or more. Claim 10 In claim 7, the unit cell is characterized by having a discharge capacity of 70 mAh / g or more after 200 cycles at a charging rate of 0.5 C and a discharging rate of 1 C.

Citation Information

Patent Citations

  • An electrolyte and a secondary lithium battery suitable for high-temperature environment

    CN108987810A

  • Anion-regulated lithium metal battery electrolyte

    CN115548437A

  • Nonaqueous electrolyte and lithium secondary battery containing the same

    KR1020150050974A

  • Use of lithium bis(fluorosulfonyl) imide (LIFSI) in non-aqueous electrolyte solutions for use with 4.2v and higher cathode materials for lithium ion batteries

    KR1020160086838A